A Critique of Prosperity Theology in the Context of Ghanaian Christianity - Boaheng, Isaac; Amoako, Clement; Boahen, Samuel (e-journal of humanitites, art and social sciences, 2023)
The economic situation in contemporary Ghana makes everyone yearn for economic progress. In Ghana, like many other parts of Africa, religion is responsible for providing the economic, spiritual, and health needs of its adherents. The predominantly Christian population in Ghana makes many people look up to Christianity to provide the road map to the country’s success. In this regard, the prosperity theology/gospel is the most dominant approach to seeking health and wealth among Ghanaian Christians. Though very persuasive, prosperity theology prompts so much debate about its influence on the religious and socio-economic life of Christians and the society at large. On the one hand, it is considered as promoting unethical behaviour and failing to yield qualitative growth for the church. On the other hand, it is considered as attracting a large following to the Christian faith. The need to evaluate the impact of this type of teaching is an urgent theological and pastoral concern because it is the most appealing Christian approach to socio-economic breakthrough for contemporary Ghanaian Christians. This paper, therefore, sought to address the problem of the lack of a balanced assessment of the prosperity gospel and how its weaknesses can be addressed. The study is a literature-based research that gathered data from publications on the subject matter. Through a critical analysis and evaluation of the information gathered, the authors evaluated the overall impact of the prosperity theology on the holistic life (social, spiritual, economic and political) of its adherents and having noted some pitfalls, recommended how this popular theology can be refined. Apart from providing guidelines for addressing the challenges associated with the prosperity theology, the paper also has the potential of yielding ethical renewal for people to live responsibly as they work toward improving their socio-economic and spiritual lives.
free